Harnessing AEM electrolyzer-level performance through strategically designing the electronic structure of electrocatalysts, enabling dynamic functional switching - Kumar, Sonu; Verma, Tushar Singh; Selvaraj, Kaliaperumal (ACS Catalysis, 2025)
The anion exchange membrane water electrolyzer (AEMWE) is a promising technology for cost-effective hydrogen production. To promote its development and adoption, targeted efforts are focused on finding non-platinum group metal (non-PGM) electrocatalysts that efficiently facilitate the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER). Nickel sulfides (NiS) are effective OER catalysts; however, they suffer due to leaching-related instability at electrolyzer stack operational conditions. We introduce a rational non-PGM design that enhances stability during the OER while excelling at the HER, showcasing molecular-level insights for a scalable AEMWE zero-gap stack device. NiS coating is applied to the Al-metal-organic framework supported by 3D porous nickel foam (NSMA), leading to charge localization at the interface, which helps in OER by requiring only 322 millivolts at 100 mA cm-2. The main innovation in the NSMA design is a controlled electroreduction process that converts the Millerite phase into Ni3S2, a catalyst (rNSMA). This transformation leads to charge delocalization at the surface and a low overpotential of -80 mV at -100 mA cm-2 for the HER. In a full cell, this catalyst duo requires an overpotential of 1.49 V, outperforming the commercial Pt/Ru catalyst pair at 1.58 V. In a scaled-up 12.96 cm2 AEM electrolyzer single-cell stack, current density rose from 398 to 1062 mA/cm2, maintained for over 100 h at high temperatures, achieving 99% Faradaic efficiency and 100% hydrogen purity. The AEM electrolyzer cell shows a good energy efficiency of 45.50 kWh/kg and a cell efficiency of 86.59%. Detailed studies, including DFT analyses, revealed that electronic structure modification enhances charge delocalization, driving its impressive performance on an industrially significant scale.
Keywords: anion exchangemembrane water electrolyzer (AEMWE); charge transfer; density functional theory(DFT); HER; nickel sulfide; OER

Strategic design of strained heterostructure anode for large-area AEM water electrolyzer via a facile etching method - Kumar, Sonu; Selvaraj, Kaliaperumal (ACS Applied Energy Materials, 2026)
Iron-based doped catalysts and various heterojunctions have been extensively studied for the Oxygen Evolution Reaction (OER). However, our understanding of the structural properties of these catalysts remains limited. Additionally, most studies have been conducted on a small scale, which restricts their practical application and potential. In this work, we designed an interface composed of Fe-doped Ni3S2 and FeOOH (FNS/NF) to function as an anode for a larger-area Anion Exchange Membrane Water Electrolyzer (AEMWE) cell. This was accomplished using the electrodeposition and electroless deposition methods at room temperature. The FNS/NF anode achieves a current density of 1 A cm-2 when paired with a standard catalyst (Pt/C) cathode, outperforming current state-of-the-art configurations that reach only 0.91 A cm-2. Furthermore, the FNS/NF anode attains over 1.3 A cm-2 when combined with our already published nonprecious metal cathode (rNSMA). This configuration exhibits a degradation rate of 1.2 mV/h after more than 100 h of stability testing, accompanied by an impressive cell efficiency of 85.40% and an energy efficiency of 38.98 kWh/kg. Comprehensive characterizations were conducted to gain a deeper understanding of the catalyst's phase characteristics, revealing that iron is in the +3 oxidation state in both FeOOH and Fe-doped Ni3S2, which forms a heterojunction. The FeOOH on the surface helps reduce the overpotential, while the Fe-doped Ni3S2 sustains performance for a longer duration.
Keywords: AnionExchange Membrane Water Electrolyzer (AEMWE); Compressive Strain; interface; Iron Oxyhydroxide; Iron-doped Nickel Sulfide; OER